2022
DOI: 10.3390/buildings12111921
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Thermal and Ventilation Indicator on University Students’ Overall Comfort

Abstract: Thermal comfort (TC) and CO2 concentration significantly influence the overall indoor comfort sensations of building occupants. However, few studies have focused on educational buildings regarding both TC and CO2 concentration in tropical regions, and they also lack guidelines for short-term evaluation, which is essential for university classrooms. In this study, a mechanically ventilated university classroom was selected to investigate the 5 min-averaged comfort ranges for indoor parameters and the impacts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Creating a favorable indoor environment is crucial for preserving human health and comfort. Extensive research has demonstrated the significant influence of the environment's quality on human life [4][5][6][7][8]. With advances in lighting technology, the scope of the lighting environment has expanded beyond the effects of artificial interior lighting to include the effects of lighting on satisfaction and comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Creating a favorable indoor environment is crucial for preserving human health and comfort. Extensive research has demonstrated the significant influence of the environment's quality on human life [4][5][6][7][8]. With advances in lighting technology, the scope of the lighting environment has expanded beyond the effects of artificial interior lighting to include the effects of lighting on satisfaction and comfort.…”
Section: Introductionmentioning
confidence: 99%